Insurance and Chain Bankruptcy Theory - Bidabad, Bijan (American Finance & Banking Review, 2019)
AbstractPurpose: This paper aims to explain the effects of the bankruptcy of one firm in other interrelated companies which are in connection with the bankrupted firm, and shows how the insurance breaks the chain of serial bankruptcy.Design: By economic analysis of insurance, the “chain bankruptcy” theory is put forward as a new theory.Findings: Through a mathematical-behavioral model, we will show how insurance breaks the chain bankruptcy in the economy.Research limitations: We have developed the case with simple modeling based on specific assumptions. In the next step, it would be extended to a more complicated and real set of assumptions.Practical implications: We show how insurance products can break serial bankruptcy in the economy.Social implications: It is shown that how insurance stabilizes the economy and make the business cycle oscillation range narrow.Originality/value: This approach is entirely different and new.Article Type: Research paper